NINA’s guidelines on environmentally responsible travel - Cimburova, Zofie; Dehnhard, Nina; Sandvik, Hanno (Norwegian Institute for Nature Research (NINA), 2020)
Cimburova, Z., Dehnhard, N. & Sandvik, H. 2021. NINA’s guidelines on environmentally responsible travel. NINA Report 1882. Norwegian Institute for Nature Research. As an institute focussing on “cooperation and expertise for a sustainable future”, the Norwegian Institute for Nature Research (NINA) has decided to implement measures that reduce NINA’s environmental footprint. This commitment encompasses the obligation to reduce the emissions of carbon dioxide (CO2) and other greenhouse gases. The greatest potential for cutting NINA’s CO2 emissions is by (1) reducing the volume of travels and by (2) changing the means of transportation for the remaining travels. With this background, NINA has adopted guidelines on environmentally responsible travel, which are described in this report. The guidelines make explicit that a journey only should be undertaken if it can be shown to create sufficient added value compared to arranging a video conference. Importantly, the further one intends to travel, the higher the added value of the journey needs to be. The guidelines provide specific examples of what constitutes an added value. For instance, listening to a conference does not create sufficient added value to justify travelling outside Europe. However, it might do so for travelling within Scandinavia. Given that a journey creates sufficient added value, the next question to be addressed is the means of transportation. Whenever possible and convenient, travels should be undertaken by train or bus, as these are the alternatives with the smallest environmental footprint by far. Train journeys of up to eight hours, and bus journeys of up to five hours, are defined as convenient in this sense. Only when travel by train or bus is unavailable or inconvenient, one may consider other means of transportation, namely car, boat or plane, in this order. The guidelines give further advice on each of the alternatives. For instance, when travelling by car, one should whenever possible share a car with other passengers. When travelling by plane, direct flights and economy class should be preferred to stopover flights and business class. Finally, the greenhouse gas emissions of car, boat and plane travels should be compensated for. The report also provides detailed information on travels between NINA’s offices (in Trondheim, Oslo, Tromsø, Lillehammer and Bergen) in terms of prices, durations and CO2 emissions. Finally, one map per NINA office illustrates the destinations that can be reached within an eight-hour train travel (or bus travel). For example, the train connections Trondheim–Oslo and Oslo–Bergen take less than eight hours, and should thus normally be preferred to air travels between these destinations. Replacing air travels by train travels along these distances reduces the CO2 emissions by 96% (or c. 120 kg per passenger). Likewise, a train travel from Oslo to Stockholm or Copenhagen takes roughly eight hours and should thus normally be preferred to a plane travel. The guidelines cover all work travels of all NINA employees beyond their hometown. Project leaders should also consult the decision tree during the early project planning stage, so as to minimise the total kilometres travelled by the project participants during the project. Ideally, the monetary costs of environmentally responsible travel should be included in the project budgets. There is no one-size-fits-all standard for travels, and it is therefore not obligatory to follow the guidelines. Rather, they form recommendations with the aim to inform and to raise awareness. Choices about travel destination and means of travel should be made consciously, since they have substantial effects on NINA’s environmental footprint. Cimburova, Z., Dehnhard, N. & Sandvik, H. 2021. NINAs veileder for miljøvennlige arbeidsreiser. NINA Rapport 1882. Norsk institutt for naturforskning. I tråd med instituttets motto – «samarbeid og kunnskap for framtidas miljøløsninger» – har Norsk institutt for naturforskning (NINA) besluttet å gjennomføre tiltak som reduserer NINAs miljø-fotavtrykk. Denne målsettinga forplikter oss til å redusere våre utslipp av karbondioksid (CO2) og andre drivhusgasser. NINAs største potensial for utslippskutt består i å (1) redusere antall reiser og (2) endre fremkomstmiddelet for de øvrige reisene. På denne bakgrunn har NINA utarbeidet en «reis bevisst»-plakat for miljøvennlige arbeidsreiser, som beskrives i denne rapporten. Ifølge «reis bevisst»-plakaten bør en reise bare gjennomføres hvis den genererer tilstrekkelig merverdi, sammenlignet med å gjennomføre et videomøte. Reisens merverdi bør være høyere, jo lenger man planlegger å reise. Veilederen inneholder noen konkrete kriterier for hva som regnes som merverdi. Å være tilhører på en konferanse genererer eksempelvis ikke nok merverdi til å rettferdiggjøre en reise utenfor Europa, men kan være god nok grunn til en reise i Norden. Gitt at en reise gir nok merverdi, er fremkomstmiddelet det neste spørsmålet man må ta stilling til. Så sant det er mulig og praktisk gjennomførbart, bør man reise per tog eller buss, fordi disse har det desidert laveste miljøfotavtrykket. Togreiser på opptil åtte timer og bussreiser på opptil fem timer regnes i denne sammenheng som «praktisk gjennomførbare». Bare hvis tog- eller buss-reiser ikke er tilgjengelige eller praktisk gjennomførbare, bør man vurdere andre reisemåter. Disse er – i prioritert rekkefølge – bil, båt og fly. Veilederen gir utdypende råd for hver reisemåte. Når man bruker bil, bør man for eksempel, om mulig, samkjøre med andre. Tar man fly, bør man foretrekke flyruter uten mellomlanding og kjøpe økonomi- fremfor business-billetter. Ved reiser med bil, båt eller fly bør man kjøpe kompensasjon for drivhusgassutslippene. Rapporten sammenstiller detaljert informasjon om reiser mellom NINAs kontor (i Trondheim, Oslo, Tromsø, Lillehammer og Bergen) når det gjelder priser, varighet og CO2-utslipp. Ved hjelp av kart vises alle reisemål som ligger innenfor en åtte timers togreise (eller bussreise) fra de ulike NINA-kontorene. Togreisene Trondheim–Oslo og Oslo–Bergen tar eksempelvis mindre enn åtte timer. På disse strekningene bør man derfor reise med tog istedenfor fly, noe som reduserer CO2-utslippene med 96 % (eller ca. 120 kg per passasjer). På samme måte bør reiser mellom Oslo og Stockholm eller København vanligvis foretas med tog, siden de tar rundt åtte timer. «Reis bevisst»-plakaten gjelder for alle arbeidsreiser som NINAs ansatte gjør utover sine hjemsteder. Prosjektledere bør dessuten bruke «reis bevisst»-plakaten tidlig i prosjektplanlegginga, slik at prosjektdeltagernes totale reiselengde kan minimeres. Helst bør også prisen for miljøvennlige arbeidsreiser inkluderes i prosjektenes budsjetter. Det fins ikke én reisemåte som passer for alle anledninger, og veilederens anbefalinger er derfor ikke bindende. Dens mål er heller å informere og skape bevissthet. Valg av reisemål og -måter bør tas bevisst, fordi de har en enorm påvirkning på NINAs miljøfotavtrykk.